General physiology formation and development as a science in Ukraine in the XIXth – during the 30-ies of the XXth century - Shulha, V. P.; Шульга, В. П.; ORCID: https://orcid.org/0000-0003-4356-7288 (Skhidnoievropeiskyi Istorychnyi Visnyk. – 2020. – 16. – 36-49, 2020)
Метою статті є висвітлення основних періодів і тенденцій розвитку загальної фізіології в Україні ХІХ – 30-х рр.. ХХ ст. на тлі розвитку світової біологічної думки.

The purpose of the article is to highlight the General Physiology development main periods and tendencies in Ukraine, summarizing the regional research and educational centers’ achievements, as well as making conclusions on individual scientists’ achievements in the XIXth – the 30-ies of the XXth century on the world biological thought development background.

Целью статьи является освещение основных периодов и тенденций развития общей физиологии в Украине XIX – 30-х гг. ХХ ст. на фоне развития мировой биологической мысли.
Становлення і розвиток загальної фізіології як науки на теренах України в ХІХ – 30-х рр. ХХ ст.
Shulha, V. General physiology formation and development as a science in Ukraine in the XIXth – during the 30-ies of the XXth century / Volodymyr Shulha // Skhidnoievropeiskyi Istorychnyi Visnyk. – 2020. – 16. – 36-49. – DOI: 10.24919/2519-058x.16.210908.
Shulha, V. (2020). General physiology formation and development as a science in Ukraine in the XIXth – during the 30-ies of the XXth century. Skhidnoievropeiskyi Istorychnyi Visnyk [East European Historical Bulletin], 16, 36–49. doi: 10.24919/2519-058x.16.210908.
Keywords: Медичні науки. Medical sciences. Медицинские науки; Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; publikatsii u WoS; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; higher education; scientific research; physiology; medicine; labor protection; biophysics; nervous system; endocrinology; human; вища освіта; наукові дослідження; фізіологія; медицина; охорона праці; біофізика; нервова система; ендокринологія; людина; высшее образование; Історія. History. История; научные исследования; физиология; медицина; охрана труда; биофизика; нервная система; эндокринология; человек